Logistics of Implementing a Large-scale Typhoid Vaccine Trial in Kathmandu, Nepal. (7th March 2019) - Colin-Jones, Rachel; Shakya, Mila; Voysey, Merryn; Theiss-Nyland, Katherine; Smith, Nicola; Pant, Dikshya; Liu, Xinxue; Tonks, Susan; Mazur, Olga; Farooq, Yama G; Kelly, Sarah; Adhikari, Anup; et al.
Abstract: Typhoid fever is estimated to affect over 20 million people per year worldwide, with infants, children, and adolescents in south-central and southeast Asia experiencing the greatest burden of disease. The Typhoid Vaccine Acceleration Consortium (TyVAC) aims to support the introduction of typhoid conjugate vaccines into Gavi-eligible countries in an effort to reduce morbidity and mortality from typhoid. TyVAC-Nepal is a large-scale, participant- and observer-blind, individually randomized, controlled trial evaluating the efficacy of a newly developed typhoid conjugate vaccine in an urban setting in Nepal. In order to effectively deliver the trial, a number of key elements required meticulous planning. Public engagement strategies were considered early, and involved the implementation of a tiered approach. Approximately 300 staff were employed and trained in order to achieve the mass vaccination of 20 000 children aged 9 months to ≤16 years old over a 4-month period. There were 19 vaccination clinics established across the Lalitpur metropolitan city in the Kathmandu valley. Participants will be followed for 2 years post-vaccination to measure the rate reduction of blood culture–confirmed typhoid fever in the vaccination arm as compared to the control arm. The experience of conducting this large-scale vaccine trial suggests that comprehensive planning, continuous monitoring, and an ability to adapt plans in response to feedback are key.